Does spatial ability help the learning of anatomy in a biomedical science course?. Issue 4 (12th November 2013) - Sweeney, Kevin; Hayes, Jennifer A.; Chiavaroli, Neville
<x xml:space="preserve">Abstract</x> A three‐dimensional appreciation of the human body is the cornerstone of clinical anatomy. Spatial ability has previously been found to be associated with students' ability to learn anatomy and their examination performance. The teaching of anatomy has been the subject of major change over the last two decades with the reduction in time spent on dissection and greater use of web‐based and computer‐based resources. In this study, we examine whether the relationship between spatial ability and performance in anatomy examinations is sustained in a contemporary curriculum. A comparison of students' performance in a series of tests of spatial ability to their anatomy examination scores in biomedical sciences course exhibited only weak association (r = 0.145 and P = 0.106). This has implications for the use of spatial ability as a predictor of success in introductory subjects in the teaching of anatomy. Anat Sci Educ 7: 289–294. © 2013 American Association of Anatomists.